One Vs. Many: who wins? An empirical investigation of online product display. Issue 3 (27th May 2019) - Kolesova, Svetlana; Singh, Reema
ABSTRACT: This study questions the unharmonious ways of product displays in online grocery retailing and aims to find if visual complexity of the product display has any impact on behavioral outcomes of online grocery shoppers. Our main finding was that visually complex images, i.e. images with a high number of elements have a negative effect on affective and cognitive states resulting in decreased behavioral intentions. However, when the number of elements in the product display was decreased, i.e. the visual complexity of the product display was reduced, shoppers' cognitive and affective responses and intentions were similar to when they were exposed to noncomplex images. We also found that arousal and pleasure (parallel mediators) absorption, telepresence, utilitarian and hedonic values and perceived ease of use (serial mediators) mediate the effect that the product display has on behavioral intentions.